Cidadania financeira ou financeirização da cidadania? : uma leitura crítica da visão de cidadania no Banco Central do Brasil sob a ótica da administração pública societal - Ricardo Vinicius Cornélio dos Santos e Carvalho (2019)
Financial citizenship is a concept that has become preeminent after the 2008 economic crisis, being developed under the influence of the dual process of financialization and increasing inequality that characterizes today’s capitalism. In Brazil, its Central Bank is currently responsible for its formulation and dissemination. The main goal of this research, therefore, is to understand how this concept was brought to the Brazilian society, investigating the reasons that led this citizenship agenda to be adopted by an institution traditionally averse to sociopolitical issues of this kind. To do so, we assume that citizenship and Public Administration have an intrinsic relationship. A bond that was weakened by managerialism but that has been recovered by the Brazilian theory of Societal Public Management, a theory that highlights the sociopolitical dimension of Public Administration. With Critical Theory underpinnings, a perspective that comprehend social phenomena as historical and dialectally determined, this research paper draws back the origins of current citizenship and Public Administration (bureaucracy) to the Modern Era, which was influenced, in its turn, by the early concepts on these issues of the Classical Antiquity. Habermas critique of Modernity, a dialogue with Max Weber’s instrumental and substantive rationality, and Hannah Arendt’s right to have rights, are used to discuss the traditional sense of citizenship given by Thomas H. Marshall, an heir of the Modern concept of citizenship viewed as a linear progressive evolution of civil, political and social rights. After this general discussion, the Brazilian history of citizenship and Public Administration is presented with a summary of Brazilian scholar’s debate about them. At the end, the Brazilian historical analysis, its theoretical debate, and the interviews of 25 leaders of Central Bank of Brazil (CBC) demonstrate that financial citizenship was not a spontaneous act of sociopolitical engagement in CBC. It was the result of a dispute in society between democratic-participatory, authoritarian and neoliberal political projects, as part of a long dialectical struggle between authoritarianism and democracy, politics and technique, developmentalism and liberalism, public and private. It is a concept-synthesis of a process that is, in fact, the financialization of citizenship, mediated by a bureaucracy whose technocratic leadership does not incorporate the sociopolitical dimension claimed by the Societal Public Management, and that establishes financial resource management as a requirement to enjoyment of rights, transforming the right to have rights into have money to have rights.